Human thermal comfort - Parsons, K. C. (Boco Raton, FL : Tayor and Francis Group, LLC, 2020)
"The book begins with current knowledge and understanding of thermal comfort and its application to providing thermal conditions for indoor and outdoor environments. It integrates and presents new ideas to provide a comprehensive model of thermal comfort so that we can move on from the 20th and early 21st century and provide a focus for developments for future decades"--
Keywords: Temperature -- Physiological effect -- Mathematical models; Environmental engineering